Rekam Medis Elektronik Terintegrasi Pada Puskesmas di Karanganyar Berbasis Pemrograman Java - Khadarusman, Rizal; , Nurgiyatna, S.T., M.Sc., Ph.D (2015)
Now is needed technology to fill the medical record, save and take it in a short time which is electronic medical record that became the solution. When a medical record is integrated with one clinic to another patient no need to bring their data to everywhere. The method of this research is SLDC (Sistem Development Life Cycle) which this method explain about sistem development life cycle of arranging and built the information sistem in order that this application more conceptual. Application feature of the Electronic Medical Record at Clinic Karanganyar Regency android-based using Java Language Programming include search, find then export patient data to PDF, doctor medical record, laboratory checking and medicine data. This application also could manage password from each username and add doctor's name, disease name, action and medicine name. Based on the references value results from a questionnaire reliability indicates the value 0,778 when matched against the criteria of reliability index tabel at intervals 0,799-0,600 this application are entered on criteria of "high". In order to, the researchers concluded that the research objectives have been achieved. Keywords: Medical Record, Electronic Medical Record, SDLC, Java, Feature, jComboBox, Reliability.